2007
DOI: 10.1590/s0100-40422007000500028
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização do complexo de inclusão ropivacaína: beta-ciclodextrina

Abstract: Recebido em 17/7/06; aceito em 1/12/06; publicado na web em 24/7/07 CHARACTERIZATION OF THE INCLUSION COMPLEX ROPIVACAINE: β-CYCLODEXTRIN. Ropivacaine (RVC) is a widely used local anesthetic. The complexation of RVC with β-cyclodextrin (β-CD) is of great interest for the development of more efficient local anesthetic formulations. The present work focuses on the characterization of the RVC:β-CD complex by nuclear magnetic resonance (NMR). The stoichiometry of the complex is 1:2 RVC:β-CD. DOSY-NMR shows that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
1
8
0
6
Order By: Relevance
“…Oxethazaine is the amino‐amide anaesthetic agent of higher lipophilicity (log P 3.64); since K is directly correlated with lipophilicity (as demonstrated for complex non‐steroid anti‐inflammatory drugs), we expected the highest association constant for OXZ among the amino‐amide group. In accordance, the association constant of OXZ with HP‐β‐CD (pH 7.4 – DOSY‐NMR) is higher than S‐bupivacaine ( K = 91/M), S‐ropivacaine ( K = 55/M) and prilocaine ( K = 41/M).…”
Section: Discussionsupporting
confidence: 63%
“…Oxethazaine is the amino‐amide anaesthetic agent of higher lipophilicity (log P 3.64); since K is directly correlated with lipophilicity (as demonstrated for complex non‐steroid anti‐inflammatory drugs), we expected the highest association constant for OXZ among the amino‐amide group. In accordance, the association constant of OXZ with HP‐β‐CD (pH 7.4 – DOSY‐NMR) is higher than S‐bupivacaine ( K = 91/M), S‐ropivacaine ( K = 55/M) and prilocaine ( K = 41/M).…”
Section: Discussionsupporting
confidence: 63%
“…Longitudinal relaxation times (T 1 ) are known to be strongly affected by the local environment of the 1 H nucleus, decreasing as it interacts with the molecular net around it [47] . In this way, T 1 values measured from the 1 H‐NMR spectrum of guest compounds are expected to decrease upon complexation with CDs [41,48] . The T 1 values of the RF aromatic hydrogens 6–9, measured in the presence and absence of β CD are presented in Figure 3; unfortunately, superposition of peaks did not allow precise measurement of the T 1 value for the ribityl RF hydrogens.…”
Section: Resultsmentioning
confidence: 99%
“…[47] In this way, T1 values measured from the 1 H-NMR spectrum of guest compounds are expected to decrease upon complexation with CDs. [41,48] The T1 values of the RF aromatic hydrogens 6-9, measured in the presence and absence of bCD are presented in Figure 3; unfortunately, superposition of peaks did not allow precise measurement of the T1 value for the ribityl RF hydrogens. No changes were detected in the T1 values of hydrogens belonging to the methyl groups of the aromatic carbons 7 and 8 ( Figure 3) or adjacent aromatic hydrogens, at carbons 6 and 9 of RF.…”
Section: The Non-inclusion Hypothesismentioning
confidence: 99%
“…Local anesthetics (LAs) are drugs that block the sensation of pain because of their influence on the voltage‐dependent sodium channel of neuronal membranes, preventing the influx of sodium ions and the propagation of nerve impulses 1–3. Recent studies have shown that LA interact with sodium channels in both ionized and nonionized states, stabilizing the membrane potential by blocking nervous conduction 4…”
Section: Introductionmentioning
confidence: 99%